Improving breast and lung cancer services in hospital using experience based co-design (EBCD). (1st April 2011) - Wiseman, T; Tsianakas, V; Maben, J; Robert, G; Richardson, A
Abstract : Abstract: Background and aims: This project sought to design better experiences for patients and health care staff from the breast and lung cancer services within two large teaching hospitals in England. Experience based co-design (EBCD) was the chosen action research approach.1 EBCD is a new and innovative methodology combining (1) a user-centred orientation (by adopting a narrative storytelling approach) and (2) a participatory, collaborative change process, allowing staff to 'see the person in the patient' and placing patient and staff experience at the centre of service development. Methods and results: The project involved an in-depth qualitative study of how care was delivered by staff and received by patients, focusing on patients' emotional 'journey'. It included 36 filmed patient narratives, capturing the key emotional 'touch points', 60 staff interviews about their experience of providing services, and ethnographic observation of clinical areas. Patient and staff interviews were analysed to identify themes and issues for which were feedback to patients and staff at various group events. For example, a composite 30 min film of breast and lung cancer patients' experiences, was created and used to feedback patient narratives to staff. Through a facilitated three-stage change process which will be described, patients and staff agreed on joint priorities for improvement and then worked together in co-design groups that focused on identified priority areas (for example information provision, day surgery, continuity of care, diagnosis and outpatient care). Discussion and conclusions: The paper reflects on lessons learned for improving patient/staff experiences through the use of EBCD. It explores the value of the EBCD approach, the use of narratives, observation and film (excerpts will be shown) as a way of humanising health care and engaging staff and patients in a change process to facilitate meaningful and lasting improvements in service provision.